Endoscopic management of cystic duct stones and Mirizzi’s syndrome: experience at an academic medical center - Pawa, Rishi; Dorrell, Robert; Pawa, Swati (Endoscopy International Open, 2022)
Background and study aims Cystic duct stones (CDS) are challenging to treat with conventional ERCP techniques due to the small diameter and tortuous nature of the cystic duct. There have been limited studies focused on endoscopic management of CDS. We present our experience managing CDS endoscopically and demonstrate that new advances in endoscopic technology have rendered CDS easier to manage.Patients and methods From 2013 to 2020, we prospectively maintained a database of patients undergoing endoscopic management of CDS. ERCP was performed in all patients, and if unsuccessful in removing stones, cholangioscopy with electrohydraulic lithotripsy (EHL) was utilized. All patients were followed in clinic for outcomes.Results Of 5,123 ERCPs performed at our institution during the study period, 21 patients were diagnosed with CDS. Six patients were successfully treated with conventional ERCP alone. Cholangioscopy with EHL was used in 15 patients undergoing 18 procedures to achieve stone clearance. CDS clearance was achieved in all patients. There was one adverse event (post-ERCP pancreatitis). Spyglass DS was associated with a significant decrease in average procedure time in comparison to first-generation SpyGlass (89.3 vs. 54.4 minutes, P = 0.004). Thirteen patients (87 %) were discharged from the hospital within 24 hours. The median follow-up duration was 23.2 months.Conclusions Endoscopy should be the preferred management strategy for CDS, especially in patients with prior cholecystectomy. Surgical outcomes have been associated with high patient morbidity and hospital length of stay. Our case series is the largest cohort of CDS patients successfully managed with cholangioscopy and EHL in the United States.